2017
DOI: 10.1039/c7ra05592g
|View full text |Cite
|
Sign up to set email alerts
|

A review of nanomaterials for nanofluid enhanced oil recovery

Abstract: Utilizing nanomaterials in flooding techniques has the potential to enhance oil recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 75 publications
0
72
0
1
Order By: Relevance
“…In addition, particle‐stabilized emulsions, also known as Pickering emulsions, have been developed rapidly in recent years. It has been suggested that the nanoparticles can improve the thermal stability and viscosity of O/W emulsions, and they are suitable for enhanced oil recovery (EOR) applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, particle‐stabilized emulsions, also known as Pickering emulsions, have been developed rapidly in recent years. It has been suggested that the nanoparticles can improve the thermal stability and viscosity of O/W emulsions, and they are suitable for enhanced oil recovery (EOR) applications …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the nanoparticles can improve the thermal stability and viscosity of O/W emulsions, and they are suitable for enhanced oil recovery (EOR) applications. 17,18 Although there have been developments in this field, some fundamental aspects of emulsion seepage and the mechanism of emulsion enhancing oil recovery remain unclear. In this paper, the emulsion formation mechanism, rheological properties, stability, seepage characteristics, and enhanced oil recovery are investigated in detail, and the Pickering emulsion for application in enhanced oil recovery is also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The size of nanoparticles is 1-100 nm, which is smaller than the pore and throat sizes [7]. As experimental studies have given in-depth analyses of NP-assisted EOR techniques, different article reviews that have been published have discussed the progress in experimental and theoretical studies in terms of newly developed nanomaterials and their limitations, as well as the challenges ahead [2,4,5,[7][8][9][10][11][12]. Figure 2 shows the recent research papers in nanotechnology applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, proper surface modification can control particle properties which can lead to proper emulsification, reduced particle retention, wettability alteration and stabilization of foam. A well-designed surface modified nanoparticle can change particle hydrophobicity and thus alleviate particle retention on the rock surface [46]. As careful control of emulsification and demulsification leads to delivery of nanoparticles to targeted areas in the formation.…”
Section: Modification Of Nanoparticlesmentioning
confidence: 99%
“…Hydration of nanoparticles is another major challenge encountered, ions within the clay material interact with the water leading to hydration and expansion of the d-space of the clay material [46]. To combat this problem, the use of swelling inhibitors should be employed.…”
Section: Challenges Of Nanoparticles In Altering Wettabilitymentioning
confidence: 99%